Pilose antler extracts promotes hair growth in androgenetic alopecia mice by activating hair follicle stem cells via the AKT and Wnt pathways - Wang, Fenglong; He, Gaiying; Liu, Menghua; Sun, Yanan; Ma, Shuhua; Sun, Zhenxiao; Wang, Yi (Frontiers in Pharmacology, 2024)
Background: Androgenic alopecia (AGA) is one of the most prevalent hair loss disorders worldwide. The hair follicle stem cell (HFSC) is closely related to the formation of hair follicle (HF) structure and HF self-renewal. The activation of HFSC in AGA is critical for hair growth. Pilose antler has been reported to have hair growthpromoting activity, but the mechanism of action on AGA and HFSC has not been reported.We previously extracted an active component from the pilose antler known as PAEs. In this study, we conducted experiments using AGA mice and HFSC. The effects of PAEs on hair growth in AGA mice were firstly detected, and then the mechanisms of PAEs for AGA were predicted by integrating network pharmacology and de novo transcriptomics data of pilose antler. Finally, biological experiments were used to validate the molecular mechanism of PAEs in treating AGA both in vivo and in vitro.Results: It was found that PAEs promoted hair regrowth by accelerating the activation of anagen, delaying the anagen-catagen transition. It also alleviated the morphological changes, such as hair shortening, thinning, miniaturization, and HF number reduction, and regulated the hair regeneration process of four subtypes of hair. We further found that PAEs could promote the proliferation of HFSC, outer root sheath (ORS) cells, and hair bulb cells in AGA mice. We then integrated network pharmacology and pilose antler transcriptomics data to predict that the mechanism of PAEs treatment in AGA mice is closely related to the PI3K-AKT/Wnt-β-Catenin pathways. Subsequently, it was also verified that PAEs could activate both pathways in the skin of AGA mice. In addition, we found that PAEs perhaps increased the number of blood vessels around dermal papilla (DP) in experiments in vivo. Meanwhile, the PAEs stimulated the HFSC proliferation in vitro and activated the AKT and Wnt pathways. However, the 2 proliferative activity of HFSC was inhibited after blocking the Wnt pathway and AKT activity.This study suggests that the hair growth-promoting effect of PAEs in AGA mice may be closely related to the stimulation of the AKT and Wnt pathways, which in turn activates the proliferation of HFSC.